Analisis Pengaruh Budaya Kesehatan, Kesadaran Kesehatan, dan Persepsi Produk Terhadap Konsumsi Jamu Pada Penderita Penyakit Pembuluh Darah di Bandar Lampung - Dzul Fithria Mumtazah; Iwan Eka Saputra; Endah Setyaningrum (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Vascular disease is a condition that affects the arteries or veins. Vascular disease occurs when blood vessels are weakened, blocked, or damaged. Other organs and structures of the body may be damaged by vascular disease as a result of reduced blood flow to the organs. In Lampung, patients with heart and the vascular disease reached 13.000 people. Meanwhile, herbal medicine is an alternative medicine that is commonly consumed by people to reduce the severity of the disease they suffer, including vascular disease. This study was conducted to determine the effect of individual health culture, their health awareness, and their perception of herbal products consumption to relieve and treat vascular disease. This research is quantitative. Data collected in this study is based on a questionnaire that provides the thoughts of the respondents. The result shows that health culture and health awareness do not always affect the consumption of herbal medicines. But the perception they have affects their decision in consuming herbal medicines. The herbal medicine that is top of mind for patients with vascular disease in Bandar Lampung to relieve vascular disease is garlic. Steps a product marketer of herbal medicines for blood vessels and heart should take is a positive perception in various circles, in Indonesia, especially in Bandar Lampung.